Penerapan Evidence Based Nursing Senam Hipertensi Kepada Lansia RW 03 Kel. Karyamulya Kec. Kesambi Kota Cirebon - Rita Rita; Dewi Erna Marisa; Ahmad Syaripudin; Amellia Surya Purnama; Ade Ana Fitriyana (Lembaga Pengembangan Kinerja Dosen, 2026)
Elderly are individuals aged 60 years and over and are considered to be in the final stage of the human life cycle. The classification of the elderly is divided into four categories: middle age or pre-elderly (44–60 years), elderly (60–75 years), senile (75–90 years), and long-livers for those aged over 90 years. One of the non-pharmacological therapies that can be applied to patients with hypertension is physical activity in the form of hypertension exercise. This study aimed to determine the implementation of Evidence-Based Nursing through hypertension exercise in elderly patients to control blood pressure. This study used a case study design in the form of gerontic nursing care involving two research subjects diagnosed with hypertension. Data were collected through interviews and blood pressure measurements. The results showed that after performing hypertension exercise for approximately 15 minutes, both respondents experienced a decrease in blood pressure. Mrs. M’s blood pressure decreased to 140/80 mmHg, while Mrs. J’s blood pressure decreased to 150/90 mmHg. In conclusion, non-pharmacological therapy in the form of hypertension exercise can be applied in daily life as an effort to improve a healthy lifestyle and help control blood pressure in the elderly.